PROMOTING RESIDENT SAFETY THROUGH TRAINING FOR CERTIFIED NURSE AIDES, RESIDENTS, FAMILIES, AND OMBUDSMEN. (20th December 2022) - Ross, Sarah; Cervantes, Diana; Severance, Jennifer; Knebl, Janice
Abstract: Preventing COVID-19 infections and ensuring resident safety in the nursing home (NH) setting requires collaboration among NH leadership, staff, residents, and their advocates including families, caregivers, and nursing home ombudsmen. To address this multi-collaborative need, the University of North Texas Health Science Center Geriatric Workforce Enhancement Program developed training in two focus areas. The first focused on resilience training for Certified Nurse Aides (CNAs) with the United Way that addresses factors influencing well-being, economic stability, mental health, and other social determinants. The second focused on training residents, families, ombudsmen, and other resident advocates to become active partners with NH leadership and staff in the prevention and control of healthcare acquired infections. To ensure training reflects the needs and preferences of key NH stakeholders, we developed a Nursing Home Advisory Council in partnership with state Ombudsman Programs in Texas, Louisiana, and New Mexico.